2002
DOI: 10.1148/radiol.2251011040
|View full text |Cite
|
Sign up to set email alerts
|

Proton MR Spectroscopic and Diffusion Tensor Brain MR Imaging in X-linked Adrenoleukodystrophy: Initial Experience

Abstract: In patients with X-ALD, MR spectroscopic imaging can depict abnormalities in white matter that have a normal appearance on both conventional MR and DT images; this finding suggests that it may be the most sensitive technique for detecting early abnormalities of demyelination or axonal loss in patients with X-ALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 25 publications
7
58
0
Order By: Relevance
“…For example, in 3 patients with adrenoleukodystrophy, focal T2 signal-intensity abnormalities were limited to the posterior third of the centrum semiovale, with normal MR imaging signal intensity and metabolite ratios in the anterior and middle regions. Although abnormal spectra from normal-appearing white matter have been reported in some leukoencephalopathies, 14,15 it is possible that a study probing the region of greatest metabolic abnormality would have increased power for separating leukoencephalopathies of different etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 3 patients with adrenoleukodystrophy, focal T2 signal-intensity abnormalities were limited to the posterior third of the centrum semiovale, with normal MR imaging signal intensity and metabolite ratios in the anterior and middle regions. Although abnormal spectra from normal-appearing white matter have been reported in some leukoencephalopathies, 14,15 it is possible that a study probing the region of greatest metabolic abnormality would have increased power for separating leukoencephalopathies of different etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Two multisection proton MRS imaging studies have reported similar abnormalities in white matter that has a normal appearance on conventional images in X-ALD. 25,26 The finding of a lower tNAA in NAWM indicates slight axonal damage, whereas the increases in concentrations of Cho, tCr, mIns, and Lac may represent slightly enhanced myelin turnover and astrocytic reaction, insufficient to lead to signal-intensity alterations on conventional MR imaging.…”
Section: Prediction Of Histopathology By Mr Imaging Parametersmentioning
confidence: 99%
“…In X-ALD, a strong correlation exists between NAA levels and FA, reinforcing the concept that both reflect axonal integrity. However, proton MR spectroscopic imaging reveals a low NAA level in regions with normal MR and DT imaging findings (61). In contrast, DT imaging showed no abnormalities outside the lesion on T2-weighted images.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 85%